An epidemiological study of prevalence of hypertension and its risk factors among non migratory tribal population of Mawai block of Mandla district of central India - Gupta, Vishnu K.; Rai, Neeraj; Toppo, Neelam Anupama; Kasar, Pradeep Kumar; Nema, Parul (International Journal Of Community Medicine And Public Health, 2018)
Background: Hypertension is the most recognized modifiable risk factor of CVD, stroke and end stage renal disease and it is directly responsible for 57% of all stroke and 24% of all coronary heart disease related deaths in India. There is paucity of data on hypertension among tribal population. Addiction of Nicotine and some cultural practices like alcohol intake is common in tribal, which are the known risk factor for NCDs. Therefore, the study of health status of tribal communities related to hypertension, is highly desirable and essential. The objectives of the study were to determine the prevalence of hypertension and associate risk factors among non migratory tribal population. Methods: A cross sectional study was conducted from March 2015 to February 2016 among 762 adults aged 20-65 years who were non migratory residents of Mawai block of Mandla districts, and they were selected through multi stage random sampling method. Results: Hypertension prevalence was 27.1% among study population. 82.2% study subjects had never undergone for blood pressure check-up. Prevalence was significantly associated with high age group. It was slightly more among the study subjects taking mixed diet than to pure vegetarian. Smoking and alcohol intake was found to be significantly associated with hypertension. It was more prevalent among mild and sedentary workers and association was significant with BMI ≥25. Conclusions: In the study every fourth study individual is Hypertensive, where smoking (in any form) and obesity was found as commonest risk factor for it.